Process research on micro-machining diamond microgroove by femtosecond laser. Issue 198 (4th May 2019) - Dou, Jian; Sun, Yu; Xu, Muxun; Cui, Jianlei; Mei, Xuesong; Wang, Wenjun; Wang, Xintian
Abstract: Using micro-nano processing system of 120 fs and 800 nm low-frequency femtosecond laser, the microgroove was processed on the CVD diamond. The effects of some processing parameters on the microgroove size were studied. The results showed that the depth and width of microgrooves increase with the increase of laser power, scanning times, while with the decrease of scanning speed. Moreover, the suitable scanning speed of femtosecond laser processing diamond is about 0.1 mm/s, and focusing on diamond can improve material removal efficiency and processing quality. It is indicated that these research work has certain guiding significance for processing diamond microchannels for heat dissipation of electronic chips.